Assessment of Plasma N-Terminal Pro-Brain Natriuretic Peptide and CRP in Patients with Severe Sepsis, Septic Shock and Acute Heart Failure - Rahman , Mona Mansour Abd El; Abdelhamid, Yasser Mohamed; Ishak, Marianne Fathy; Hadad, Kareem Essam Elden; Shalaan, Mohamed Shalaan Ibrahim (International Journal of Membrane Science and Technology, 2023)
Background: Increased plasma levels of brain natriuretic peptide (BNP) have been identified as predictors of cardiac dysfunction and prognosis in congestive heart failure and ischemic heart disease. In severe sepsis patients, however, no information is available yet about the prognostic value of natriuretic peptides in Egyptian patients. Aim: The aim of the present work is to study the relationship between amino-terminal pro-BNP, C-reactive protein in one hand and the severity of organ dysfunction and mortality on admission in the other in patient with severe sepsis and septic shock.Patients and methods: This study population consisted of ninety patients aged >18 years, who were admitted to the internal medicine department ICU, Kasr El-Aini Hospitals, Cairo University and enrolled within 24 hours of admission to the ICU with severe sepsis, patients with septic shock, patients with acute decompensated heart failure and patients who developed severe sepsis while in the ICU. The patients were divided to 3 groups, Group I (septic shock), group II (severe sepsis) and group III (heart failure). Plasma N-Terminal Pro-Brain Natriuretic Peptide and CRP were measured.Results: There was higher CRP level in group I (69.56 ± 38.01) compared to group II (41.70 ± 25.34) with a significant p value (0.002). There was higher level of NTproBNP in group I (2809.73 ± 2362.32 pg/ml) compared to group II (2595.13 1968.39 pg/ml) and group III (789.37 ± 348.01pg/ml) with a statistically significant p valueConclusion: NT-pro BNP values are increased in severe sepsis and septic shock. Values are significantly higher in non survivors than survivors. Elevated concentrations of serum CRP on admission are indicators of an increased risk of severe sepsis, septic shock and death.